Core-shell electrospun fibers for delivery of hydrophilic drugs - Wong, Yin Cheng (2018)
The current mode of insulin delivery for diabetic patients is through subcutaneous injection, which is invasive, inconvenient and causes infections. Although oral delivery of insulin may allow better patient compliance due to ease of administration, it is very challenging due to low bioavailability as insulin will degrade in the acidic stomach environment. Much research has been done on alternative methods to deliver insulin which are non-invasive, one of which is through buccal delivery. Core-shell nanofibers spun using a co-axial electrospinning technique have been found to have the ability to control the drug release. In this project, electrospun core-shell nanofibers were fabricated using a co-axial electrospinning technique. The nanofibers consist of a core loaded with insulin and a shell composed of a blend of pH-responsive polymers (i.e. Eudragit) which can potentially control the rate of drug release. Eventually, the core-shell nanofibers can be placed on the buccal tissue and may deliver the insulin through the buccal mucosa as the nanofibers dissolve in the saliva. Optimization and characterisation of the electrospun core-shell nanofibers were done using confocal microscopy and scanning electron microscopy. The drug release behaviours of monolithic and core-shell nanofibers were studied by dissolving them in simulated saliva and measuring the amount of insulin released. The drug release results show that the core-shell nanofibers dissolved over an extended period of time and were able to maintain a sustained release, whereas the monolithic nanofibers dissolved instantly to give a burst release. This demonstrates the important role that the Eudragit shell plays in the ability of the core-shell nanofibers to control drug release. However, the measured drug encapsulation of the core-shell nanofibers was very low. Overall, the core-shell nanofibers have the potential to control the release of the insulin but further optimization and investigation to need to be done to improve the drug release.